Pendampingan Kegiatan Implementasi Seni Mengajar Berbasis Peer Teaching di TK Al Munawar Tulungagung - Dita Hendriani; Dwi Junianto; Ella Rolita Arifianti; Pangki Suseno; Yeni Roha Mahariani (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The peer teaching method is a strategic learning tool for creating a conducive learning environment, allowing students to play an active role and fostering connectivity between students. This method can be used as an alternative in classroom learning activities where students with the ability can act as tutors. This activity was carried out at AL Munawar Kindergarten in Tulungagung, with stages ranging from planning, training implementation, mentoring, and evaluation. The results of the community service activities were an increase in student abilities, learning outcomes, active and critical thinking skills, and communication skills. To achieve these results, strategic efforts are needed, starting from curriculum development, improving teacher competence, and providing learning facilities. Although it still has a number of weaknesses, including the difficulty of finding the right tutor who is confident and capable of mastering the material, the peer teaching method can be used as a reference for effective learning media in nurturing and developing students.